2019
DOI: 10.1037/spy0000157
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of groupness during fitness classes positively predict recalled perceptions of exertion, enjoyment, and affective valence: An intensive longitudinal investigation.

Abstract: Group contexts such as fitness classes are popular forms of physical activity, and studying them can uncover new ways to promote exercise adherence. Focusing on the potential for group fitness experiences to vary from class to class, we examined how exercisers' dynamic perceptions of groupness relate to recalled perceptions of exercise enjoyment, affective valence, and exertion. These outcome variables are in focus because they are theoretically construed to be determinants of physical activity. Using an inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 56 publications
(84 reference statements)
3
28
0
2
Order By: Relevance
“…Utilizing the 10-item version previously identified in study 1 (removing “burn some calories,” “lay down,” and “rest my body”) lead to an improved, good fitting model (TFI/CFI: 0.91/0.93; RMSEA: 0.08; SRMR: 0.04). For the final model, X 2 (148) = 603.9, p < .001.Items loaded similarly to Study 1 (see Table 4), with interpretable “Move” and “Rest” latent variables in both the Right Now and Past Week timepoints. Removal of multivariate outliers slightly worsened model fit but not did substantively change them (all goodness-of-fit indices within desired parameters); thus, outliers were retained.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Utilizing the 10-item version previously identified in study 1 (removing “burn some calories,” “lay down,” and “rest my body”) lead to an improved, good fitting model (TFI/CFI: 0.91/0.93; RMSEA: 0.08; SRMR: 0.04). For the final model, X 2 (148) = 603.9, p < .001.Items loaded similarly to Study 1 (see Table 4), with interpretable “Move” and “Rest” latent variables in both the Right Now and Past Week timepoints. Removal of multivariate outliers slightly worsened model fit but not did substantively change them (all goodness-of-fit indices within desired parameters); thus, outliers were retained.…”
Section: Resultsmentioning
confidence: 85%
“…Future research should aim to understand how desires to move and rest vary across the day with arousal, energy, fatigue, distress and other components of affect. It would be useful to determine what other factors affect movement desires, such as environmental cues, such as lighting (147), music (37, 38), social interactions (148), et cetera (24, 146).…”
Section: Studymentioning
confidence: 99%
“…Future research should aim to understand how desires to move and rest vary across the day with arousal, energy, fatigue, distress and other components of affect. It would be useful to determine what other factors affect movement desires, such as environmental cues like lighting ( Dunai et al, 2007 ), music ( Levitin et al, 2018 ; Matthews et al, 2019 ), social interactions ( Graupensperger et al, 2019 ), et cetera ( Stults-Kolehmainen et al, 2013b ; Papies and Barsalou, 2015 ). It can be said with near certainty, however, that desires/wants to move and rest fluctuate across time and capture a motivational state.…”
Section: Discussionmentioning
confidence: 99%
“…al (2017) found that stronger identification with the parkrun running group positively predicted participation, life satisfaction, exercise-specific satisfaction, and group cohesion. These and other studies (Carnes & Mahoney, 2016;Graupensperger et al, 2019) (Carnes & Mahoney, 2016) offer support for the idea that individuals' perceptions of the social group as cohesive and supportive, and with which they can strongly identify as group members, can promote positive affective exercise experiences, increase participation in physical activity, and facilitate performance via socially-mediated mechanisms other than arousal, evaluation apprehension and distraction. This literature has elucidated the types, causes and consequences of group cohesion in sports.…”
Section: Introductionmentioning
confidence: 57%